2021
DOI: 10.1186/s13358-020-00215-7
|View full text |Cite
|
Sign up to set email alerts
|

Failed prey or peculiar necrolysis? Isolated ammonite soft body from the Late Jurassic of Eichstätt (Germany) with complete digestive tract and male reproductive organs

Abstract: Ammonoid soft parts have been rarely described. Here, we document the soft parts of a perisphinctid ammonite from the early Tithonian of Wintershof near Eichstätt (Germany). This exceptional preservation was enabled by the special depositional conditions in the marine basins of the Solnhofen Archipelago. Here, we document this find and attempt to homologize its parts with various organs such as the digestive tract, reproductive organs, the mantle cavity with gills, and the hyponome, with differing degrees of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…For example, many belemnites demonstrably can be classified as pabulites in such cases, where the rostrum cavum is fragmented (Klug et al, 2010;Schweigert, 1999Schweigert, , 2018. Isolated soft parts of an ammonite from the Late Jurassic of Germany described by Klug et al (2021b) are likely also a pabulite. There are countless examples-few of them published or displayed-of incompletely preserved vertebrate remains from the Late Jurassic Solnhofen-type limestones, such as isolated heads, fins or tails of fishes (e.g., Chellouche, 2016;Dietl & Schweigert, 2011;Maxwell et al, 2021) as well as almost complete but lethally bitten fish, in one case leaving a mortichnium (Schweigert et al, 2016), or even large parts of marine crocodiles (Dietl & Schweigert, 2011;Mäuser, 2015), and abundant crushed ammonite shells (Klug et al, 2021b).…”
Section: Leftover Falls Turn Into Pabulitesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many belemnites demonstrably can be classified as pabulites in such cases, where the rostrum cavum is fragmented (Klug et al, 2010;Schweigert, 1999Schweigert, , 2018. Isolated soft parts of an ammonite from the Late Jurassic of Germany described by Klug et al (2021b) are likely also a pabulite. There are countless examples-few of them published or displayed-of incompletely preserved vertebrate remains from the Late Jurassic Solnhofen-type limestones, such as isolated heads, fins or tails of fishes (e.g., Chellouche, 2016;Dietl & Schweigert, 2011;Maxwell et al, 2021) as well as almost complete but lethally bitten fish, in one case leaving a mortichnium (Schweigert et al, 2016), or even large parts of marine crocodiles (Dietl & Schweigert, 2011;Mäuser, 2015), and abundant crushed ammonite shells (Klug et al, 2021b).…”
Section: Leftover Falls Turn Into Pabulitesmentioning
confidence: 99%
“…With their pointed beaks (Klug et al, 2010(Klug et al, , 2020Keupp & Mitta, 2015;Lehmann et al, 2016), they were able to hold, immobilize and cut prey. Recently, it was suggested that they might have been able to break ammonite conchs in order to facilitate withdrawal of the soft parts (Klug et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…According to phylogenetic bracketing, it is generally assumed that they had ten arms 1 , 2 . However, no remains of arms or arm structures have ever been discovered in ammonites, not even when internal organs are preserved 3 . This is most probably due to the retraction of the arms into the body chamber post-mortem 1 , and/or the poor preservation potential of the arms’ soft tissue 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the soft parts of coleoid cephalopods (belemnites, squids, and octopuses) and in spite of the great abundance of ammonoid fossils, reports on ammonoid soft parts are very limited in number (see, e.g., Klug & Lehmann, 2015;Klug et al, 2008Klug et al, , 2016Klug et al, , 2021Polizzotto et al, 2015;Tanabe, Sasaki, et al, 2015). The scarcity of soft tissue preservation in ammonoids is often explained by the buoyancy apparatus, which prevents the carcasses from rapid burial.…”
Section: Introductionmentioning
confidence: 99%
“…The chitin makes these parts more resistant against decomposition when compared to non-sclerotized soft tissues. Accordingly, these are the most widely reported organic hard components of soft tissues (Closs, 1967a(Closs, , 1967bHollingworth & Hilton, 1999;Klug & Jerjen, 2012;Klug & Lehmann, 2015;Klug et al, , 2016Klug et al, , 2021Kruta et al 2011Kruta et al , 2020Landman et al, 2010;Lehmann, 1981;Lehmann & Weitschat, 1973;Mapes et al, 2019;Tanabe, Kruta, et al, 2015;Wippich & Lehmann, 2004). Besides, a few records exist for the presence of ammonoid gills (Klug et al, 2021;Lehmann, 1985;Lehmann & Weitschat, 1973;Mironenko, 2015), and siphuncle (Mironenko, 2017 and references therein;Tanabe et al, 1982Tanabe et al, , 2000Tanabe, Sasaki, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%